Technology Implementation in the Process of Higher Education: Issues and Opportunities - Ding, Shaojie; Pavliuk, Olena; Lysenko, Tetiana; Hetmanenko, Liudmyla (Journal of Posthumanism, 2025)
The digitalization of higher education is one of the key components of the global educational transformation, which ensures accessibility, flexibility and personalization of learning. In the context of the development of the information society and the growing role of digital technologies in ensuring the competitiveness of graduates, the issue of effective integration of digital tools into the educational process is becoming particularly relevant. The purpose of the study is to analyze the current state, challenges and prospects of integrating digital technologies into the higher education process in Ukraine. The methodological basis of the work is a systematic approach that allows us to consider the digitalization of education as a complex process of transformation of all components of the educational environment, using the methods of content analysis of scientific sources, comparative analysis of international practices and generalization of empirical data. The study identifies the main areas of digitalization of higher education in Ukraine, including the introduction of learning management systems (LMS), the development of blended learning, the creation of electronic learning environments, and the use of artificial intelligence to personalize learning. The author identifies key barriers to digitalization, including insufficient digital competence of individual teachers, limited funding, uneven access to quality Internet, and the lack of a unified digital educational ecosystem. Particular attention is paid to analyzing the impact of global crises, in particular the COVID-19 pandemic and the military actions in Ukraine, on accelerating digital transformation in higher education. The practical significance of the results obtained is to develop recommendations for improving the efficiency of digital transformation of higher education institutions, in particular through the development of digital competencies, the creation of a single national online learning platform and the introduction of mechanisms for monitoring the quality of the digital educational environment. The presented comprehensive approach to the analysis of digitalization can be used as a basis for the formation of strategic directions for the development of higher education in Ukraine in the digital era.